2023
DOI: 10.3390/app13032005
|View full text |Cite
|
Sign up to set email alerts
|

Improving Classification Performance with Statistically Weighted Dimensions and Dimensionality Reduction

Abstract: In image classification, various techniques have been developed to enhance the performance of principal component analysis (PCA) dimension reduction techniques with guiding weighting features to remove redundant and irrelevant features. This study proposes the statistically weighted dimension technique based on three distribution-related class behaviors; collection-class, inter-class, and intra-class to enhance the feature-extraction ability before using PCA for feature selection. The data from the statistics-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Machine learning algorithms play a vital role in diverse fields by enabling predictions and pattern discovery from vast datasets [21] - [23]. However, the curse of dimensionality presents challenges such as increased computational complexity and potential overfitting.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning algorithms play a vital role in diverse fields by enabling predictions and pattern discovery from vast datasets [21] - [23]. However, the curse of dimensionality presents challenges such as increased computational complexity and potential overfitting.…”
Section: Introductionmentioning
confidence: 99%
“…Further research showed that near the optimal drilling operating mode, the accompanying measured signal has typical identifiable and classifiable characteristics. A recent study [16] proposed a technique to improve the feature extraction capability before using the PCA method for feature selection. The authors of the manuscript deal with the scientific topic of effective control of the drilling process based on the classification of vibration signals from the aggregates of the drilling stand.…”
Section: Introductionmentioning
confidence: 99%